1999
DOI: 10.2307/1468463
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Limitation of Algal Biomass Accrual in Streams: Seasonal Patterns and a Comparison of Methods

Abstract: In-situ, nutrient amendment experiments (nutrient-diffusing substrata, NDS) were conducted in 12 New Zealand gravel-bed streams to investigate seasonality of biomass accrual and nutrient limitation of benthic algal communities. Benthic algal biomass accrual rates exhibited significant (p = 0.019, repeated measures ANOVA) seasonal differences; rates were greatest in summer and least in winter. The degree of nutrient limitation also differed (p = 0.003) seasonally; periphyton community biomass was most responsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
108
0
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(118 citation statements)
references
References 44 publications
7
108
0
3
Order By: Relevance
“…3). Increased benthic algal growth at enhanced nutrient supply is a wellknown phenomenon (Francoeur et al, 1999). We found an increased rate of microbial degradation (fine mesh bags) in the nutrient treatments (Tab.…”
Section: Effects Of Flow Increase and Nutrients On Leaf Litter Degradsupporting
confidence: 51%
“…3). Increased benthic algal growth at enhanced nutrient supply is a wellknown phenomenon (Francoeur et al, 1999). We found an increased rate of microbial degradation (fine mesh bags) in the nutrient treatments (Tab.…”
Section: Effects Of Flow Increase and Nutrients On Leaf Litter Degradsupporting
confidence: 51%
“…4). Had productivity been limited by one nutrient or the other, ambient availability of the nonlimiting nutrient should have allowed at least a small response to addition of the limiting nutrient alone, as is often observed (Francouer 2001).…”
Section: Discussionmentioning
confidence: 88%
“…Thus, early in the study nutrient ratios did not indicate which nutrient would limit periphyton accrual. A recent study in New Zealand streams also found N : P ratios in stream water and periphyton to be of limited use in predicting nutrient limitation (Francoeur et al 1999). On days 17 and 28 of our study there was some indication that algae may have responded to P concentration, as biovolume was lowest at the lowest P concentration (ambient treatment).…”
Section: Discussionmentioning
confidence: 99%